2002
DOI: 10.1007/s00436-002-0634-3
|View full text |Cite
|
Sign up to set email alerts
|

Nasal schistosomes of wildfowl in the Czech Republic

Abstract: In Central Europe, the adults of nasal bird schistosomes of the genus Trichobilharzia have only been reported from experimental infections. Our work confirmed a relatively high prevalence of these parasites in wild anatid birds in the Czech Republic. The isolated miracidia were used to infect the Radix peregra (an autochtonous snail species) which proved to be a susceptible intermediate host. Subsequently, the emerged cercariae penetrated the skin of domestic ducks and adults were found in the nasal mucosa. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…Horák et al 2002;Kolářová et al 1997;Rudolfová et al 2002). Many of them also occur in dense populations in Iceland (Petersen 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Horák et al 2002;Kolářová et al 1997;Rudolfová et al 2002). Many of them also occur in dense populations in Iceland (Petersen 1998).…”
Section: Introductionmentioning
confidence: 99%
“…regenti were detected for example, in Iceland [15] and in France, where the prevalence on three studied localities reached 40% [9]. Based on findings of Rudolfová et al [14, 16], prevalence of T . regenti infection of waterfowl was 14% in Czech Republic (one studied locality) [16] and 22% in Gdansk area in Poland [14].…”
Section: Introductionmentioning
confidence: 99%
“…The search for schistosomes in water birds in France and Iceland in the past decade has revealed a number of species. Focusing on the nasal species, T. regenti, five final hosts have already been identified in France; A. platyrhynchos and A. fuligula, previously described by Rudolfová et al (2002) and Picard and Jousson (2001), and also C. olor, M. merganser and A. clypeata (Jouet et al 2009). In Iceland, recent molecular analyses of eggs and adult worms of a nasal Trichobilharzia found in A. platyrhynchos in Landmannalaugar, previously reported by Skírnisson and Kolářová (2008;Skírnisson et al 2009) and Aldhoun et al (2009) as undescribed species, have now confirmed that the involved species actually was T. regenti.…”
Section: Discussionmentioning
confidence: 98%
“…Previously, Palmer and Ossent (1984) had highlighted parasites from the nasal cavity of Cygnus olor from Alpine lakes. Later, birds belonging to the family of Anatidae including A. platyrhynchos, Aythya fuligula, A. ferina and Anas clypeata were found to be naturally infested with nasal Trichobilharzia (Rudolfová et al 2002). Some fragments of worms collected from these birds were analysed by molecular methods (Picard and Jousson 2001;Rudolfová et al 2007).…”
Section: Introductionmentioning
confidence: 99%